Research progress and innovative pathways for the large-scaled green and low-carbon utilization of coal-based solid wastes - Lang LIU; Mengbo ZHU; Shuangming WANG; Pan YANG; Bo YU; Shishan RUAN; Junjun YANG; Geng XIE (Meitan kexue jishu)
Coal mining and processing have provided China with reliable energy security and essential chemical raw materials, significantly driving industrial development and social progress. However, this process has also resulted in the production of large amounts of coal-based solid waste. These wastes not only occupy vast land resources but also cause varying degrees of environmental pollution, especially during long-term storage, when they may release harmful gases, heavy metals, and other toxic substances, posing a threat to water, air, and soil safety. Therefore, efficiently and large-scale utilization of coal-based solid waste has become a key technical challenge in achieving resource recycling and reducing environmental pollution. Based on an analysis of the generation, classification, characteristics, and environmental impacts of coal-based solid waste, this paper reclassifies existing coal-based solid waste and systematically summarizes its mature large-scale utilization models in areas such as mine backfilling, construction materials, and ecological restoration. It also proposes innovative pathways for the green and low-carbon utilization of coal-based solid waste. The study shows that: ① Coal-based solid waste can be classified into two categories: denatured and original coal-based solid waste, with denatured coal-based solid waste having the potential to develop cementing materials and carbon sequestration functions, while original coal-based solid waste possesses the characteristics of natural aggregates and soil materials; ② Currently, the main large-scale utilization models of coal-based solid waste include mine backfilling (such as cementing materials, paste backfilling, and grout backfilling), construction materials (such as cement supplementary materials, road materials, and precast components), ecological restoration (such as filling of subsidence areas, reclamation of wastelands, and soil improvement), and resource extraction and utilization (carbonaceous components, aluminium, sulfur and rare elements); ③ A new technology for graded, quality-specific, and full-component utilization of coal-based solid waste is proposed, which extracts high-value components and uses the remaining components for backfilling of mined-out areas, maximizing resource utilization; ④ Innovative technologies for modifying and co-disposing of high-salinity wastewater, modifying backfill for co-constructing storage facilities, and co-sequestering hazardous solid waste in functional storage are discussed. This research aims to improve the resource utilization efficiency of bulk coal-based solid waste, promote the green transformation of the coal industry, and provide new pathways for the sustainable development of coal resources.